Chylous Ascites - A Presentation of Gastric Lymphoma (Journal of Medicine, 2008)
A 47-year-old male was admitted with gradually developing ascites. Paracentesis revealed chylous fluid. Histoathology following endoscopic biopsy from the stomach was suggestive of diffuse Non-Hodgkin lymphoma, intermediate grade. Â  DOI = 10.3329/jom.v7i1.1360 J MEDICINE 2006; 7 : 36-38